2017
DOI: 10.1039/c7nr04672c
|View full text |Cite
|
Sign up to set email alerts
|

The optical response of monolayer, few-layer and bulk tungsten disulfide

Abstract: We present a comprehensive optical study of thin flakes of tungsten disulfide (WS) with thickness ranging from mono- to octalayer and in the bulk limit. It is shown that the optical band-gap absorption of monolayer WS is governed by competing resonances arising from one neutral and two distinct negatively charged excitons whose contributions to the overall absorption of light vary as a function of temperature and carrier concentration. The photoluminescence response of monolayer WS is found to be largely domin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
118
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(144 citation statements)
references
References 95 publications
(72 reference statements)
25
118
0
1
Order By: Relevance
“…Temperature dependences of the exciton and trion peak positions are fitted well with the fitting parameters listed in table 1. The values for E g (0) are comparable to those in previous studies on WS 2 monolayers [31] and indicate that the observed temperature dependence originates from the change in bandgap of WS 2 .…”
Section: Temperature-dependent Photoluminescencesupporting
confidence: 86%
See 1 more Smart Citation
“…Temperature dependences of the exciton and trion peak positions are fitted well with the fitting parameters listed in table 1. The values for E g (0) are comparable to those in previous studies on WS 2 monolayers [31] and indicate that the observed temperature dependence originates from the change in bandgap of WS 2 .…”
Section: Temperature-dependent Photoluminescencesupporting
confidence: 86%
“…The trion dissociation energy, i.e. the energy difference between the exciton and trion is related to the Fermi energy by [31,35]:…”
Section: Excitation Power Dependence Of Plmentioning
confidence: 99%
“…5(c). The X 1s A resonance undergoes a red shift from 1.196 ± 0.001 eV to 1.1307 ± 0.001 eV as the layer thickness is increased from 1L to bulk as has been observed previously also in WSe 2 [25], MoSe 2 [23], WS 2 [3] and MoTe 2 [26,44]. At the same time, the energy difference between the X 1s A and X 2s A resonances decreases from 127 meV to 25 meV as the layer thickness is increased from 2L to bulk (X 2s A is not observed for the 1L flake).…”
Section: Ssupporting
confidence: 76%
“…We calculate the g-factors of a trilayer in the same way as in the bilayer. We introduce the three sets of basis states {|Ψ (1) n }, {|Ψ (2) n }, {|Ψ (3) n }, which belong to the layers z = −l, z = 0 and z = l respectively. In this case the crystal has the mirror symmetry, with the mirror plane z = 0.…”
Section: Trilayermentioning
confidence: 99%
“…This peculiar evolution originates, as discussed previously in literature [43][44][45][46][47][48], from contribution of two different CX states to the feature observed in absorption-type spectra. The existence of two CX states in 'darkish' materials is a consequence of spin alignment in conduction subbands, which allows an excess electron from either K+ or K− valley to accompany the photo-created electron-hole pair and form a bound CX state.…”
mentioning
confidence: 71%